Romanian Theories of Central European Integration - Nastasă-Kovács, Lucian (The Development of European and Regional Integration Theories in Central European Countries, 2022)
Central Europe, especially Eastern Europe, has always been the geographic convergence point of several Great Powers that exercised their influence on the region regardless of the wishes of smaller states or national/ethnical groups. At the mid-19th century, the political equation changed, and the desire for a new regional order was emerging at the ethnic group or small nation level. Their elites proposed projects and lobbied for several political constructions that would advantage their nations and help them define their new political development with some kind of autonomy/independence. The nation states and political turmoil in the second part of the century launched several integration and political construction projects designed to reshape the face of Eastern Europe following a more realistic representation system. During the 1848 revolution, many political and intellectual elites tried to consolidate new political construction projects for the Romanian principalities or minorities in the Austro-Hungarian Empire. Central Europe became a place where the old order had reached its capabilities in managing and integrating the ethnic groups and nations in a satisfying way; imperial reflexes were no longer a solution for national inspirations. The Romanian principalities unification, the Ausglich, or the former Greek independence war, were just the tip of the iceberg of the need political reshaping in Eastern Europe. In contrast, projects like the Danube Confederation were designed to secure autonomy and replace the old imperial approaches into a fragmented region. Mitteleurope and Eastern Europe became the central point of political debates, and the need for nations to secure their future became a significant issue on the political and cultural agenda. From the Romanian point of view, Popoviciu or Maiorescu’s projects and ideas became the central point of the debate. This chapter is a chronicle of these efforts and ideas, the flow of intellectual work in the European space to reshape the Eastern European region according to the needs of small nations and ethnic groups. KEYWORDS: federalization, Danube Confederation, Popovici, Ausglich, Mitteleuropa, Eastern Europe, national aspirations, Palacky, Densusianu